First-principles Calculation of Cumene: Molecular Structure, Electronic Structures, Spectroscopic Analysis, and Thermodynamic Properties - Rana Magar, Abhishek; Ghimire, Rabin; Basnet, Bishwo; Shrestha, Prakash Man; Gupta, Suresh Prasad; Rai , Krishna Bahadur (Molung Educational Frontier, 2024)
This study uses the DFT method for the investigation of optimized structure, electronic structures, charge analysis, FT-IR, FT-Raman spectroscopic analysis and thermodynamic properties. The optimized energy and dipole moment are 9531.775 eV and 0.3818 Debye. The bond lengths of C1-C2 and C1-H7 molecules inside the benzene ring are observed to be 1.39 Å and 1.08 Å respectively. The bond angle of C1-C2-C3 and C2-C1-C6 are found to be 120.10 Å and 119.36 Å. The HOMO-LUMO energy gap is 6.331 eV which corresponds very close to the energy gap of 6.321 eV obtained from density of states. The global parameters with ionization energy value 6.747 eV, electron affinity with 0.4152 eV, chemical potential with -3.5811 eV, electronegativity with 3.5811 eV, global hardness with 3.1659 eV, softness with 0.3148 eV-1 and electrophilicity index with 2.0253 eV are obtained. The Mulliken charges analysis indicate that most of the carbon atoms except C4 and C12 are found to carry negative charges where all of the H-atoms are found having positive charge. The molecular electrostatic potential, electrostatic potential and electron density identify different electrophilic and nucleophilic region and its reactive natures. The FT-IR spectroscopy shows strong C-H vibrations at 3186-3093 cm-1, methyl group vibration at 3091-3078 cm-1 and the ring vibrations at 1641-1482 cm-1. The heat capacity at constant volume and at constant pressure, internal energy, enthalpy, entropy increase with increasing temperature. However, Gibb’s free energy shows opposite nature providing very important insights according to the change in temperature.